KAJIAN SYSTEMATIC LITERATURE REVIEW TERHADAP TERMINOLOGI RELIGIUSITAS DALAM PENELITIAN DI INDONESIA - Sugiyarto; Dwi Yuliani, Prima; Rani Gustiasari, Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Research that addresses religiosity in Indonesia amounts to tens of thousands of research titles. This shows that the theme is very interesting and has been studied from various scientific backgrounds. From the results of research using a Systematic Literature Review, it was found that there are many differences in using the concept of religiosity and they are still partial. For this reason, this Systematic Literature Review (SLR) study was carried out to obtain and reconstruct an understanding of religiosity in Indonesia from various research conducted to be more comprehensive and not partial. This SLR uses a database obtained from the search engine Harzing.com. The data obtained was then reduced using the SLR protocol until the amount was sufficient for analysis. As a result, the concept of religiosity in Indonesia does not have much debate, both in terms of terminology and definition. In contrast to abroad, which is actually secular, the debate has been long and there has been no agreement. Keywords: Studies, Systematic Literature Review, Religiosity, Diversity